PERFORMA BURUNG PUYUH (Coturnix coturnix japonica) UMUR 3 SAMPAI 6 MINGGU DENGAN POLA PEMBERIAN PAKAN BEBAS PILIH (Free choice feeding) - Asiyah, N; Sunarti, Dwi; Atmomarsono, Umiyati (Animal Agriculture Journal, 2013)
ABSTRAK The research aimed to determine the effect of feeding patterns of free choice on the performance of quail (coturnik-coturnik japonica) age d 3 to 6 Weeks preference which includes feed, feed consumption, body weight gain and feed conversion. The research was conducted in October 2011 - January 2012 at the Faculty of Animal Breeding Laboratory and Agriculture, Diponegoro University, Semarang. The material used in this study is 216 tail female quail 3 weeks old with a body weight 56.01 Â± 1.61 g (CV = 8.67%), feed ingredients used are corn, rice bran, soybean meal, coconut cake, fish meal, and PMM (Poultry Meat Meal), well additional material such as vitamins and vita stress. The equipment used is a cage, the feeding, drinking, lighting, electric scales, thermometers and hygrometers. There are three treatments with the addition of feed ingredients protein source in each treatment, T1 = 2 dietary energy source + 2 dietary protein source (rice brain, corn, fish meal, soybean meal); T2 = 2 dietary energy source + 3 dietary protein source (rice brain, corn, fish meal, soybean meal, coconut meal); T3 = 2 dietary energy source + 4 dietary protein source (rice brain, corn, fish meal, soybean meal, copra, poultry meat meal). Research use completed random design with 9 repeated. Data analysis use a variety of test and continued F Duncan test if any treatment effect. The results showed that the pattern of free choice feeding with a variety of protein sources significantly (p <0.05) feed intake, body weight growth.Keywords: female quail (coturnix coturnix japonica), free choice feeding, performanceABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pola pemberian pakan bebas pilih (free choice feeding) terhadap performa burung puyuh (coturnik-coturnik japonica) umur 3 sampai 6 Minggu yang meliputi prefrensi pakan, konsumsi pakan, pertambahan bobot badan dan konversi pakan. Penelitian dilakukan pada bulan Oktober 2011- Januari 2012 di Kandang Laboratorium Pemuliaan Fakultas Peternakan dan Pertanian, Universitas Diponegoro, Semarang. Materi yang digunakan dalam penelitian ini adalah 216 ekor burung puyuh betina umur 3 minggu dengan bobot badan 56,01 Â± 1,61 g (CV= 8,67%), bahan pakan yang digunakan adalah jagung, dedak, bungkil kedelai, bungkil kelapa, tepung ikan, dan PMM (Poultry Meat Meal), serta bahan tambahan seperti vitamin dan vita stress. Peralatan yang digunakan adalah kandang, tempat pakan, tempat minum, lampu penerangan, timbangan elektrik, termometer dan higrometer. Ada 3 perlakuan dengan penambahan bahan pakan sumber protein pada masing-masing perlakuan, yaitu T1= 2 bahan pakan sumber energi + 2 bahan pakan sumber protein (bekatul + jagung + tepung ikan + bungkil kedelai); T2= 2 pakan sumber energi + 3 pakan sumber protein (bekatul + jagung + tepung ikan + bungkil kedelai + bungkil kelapa); T3= 2 pakan sumber energi + 4 pakan sumber protein (bekatul + jagung + tepung ikan + bungkil kedelai + bungkil kelapa + PMM). Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan 9 ulangan.Data dianalisis ragam menggunakan uji F dan dilanjutkan uji Duncan apabila ada pengaruh perlakuan. Hasil penelitian menunjukkan bahwa pola pemberian pakan secara bebas pilih (free choice feeding) dengan beragam sumber protein berpengaruh secara signifikan (p<0,05) terhadap konsumsi pakan, pertumbuhan bobot badan.Kata kunci : burung puyuh betina (coturnix-coturnix japonica), pakan bebas pilih (free choice feeding), performa